2015
DOI: 10.1128/jvi.01838-15
|View full text |Cite
|
Sign up to set email alerts
|

AP-2 Is the Crucial Clathrin Adaptor Protein for CD4 Downmodulation by HIV-1 Nef in Infected Primary CD4 + T Cells

Abstract: Altogether, among the factors tested, AP-2 is the most important player for Nef-mediated CD4 downmodulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
2
13
0
4
Order By: Relevance
“…Recently, AP‐2 has been confirmed as the crucial AP complex hijacked by Nef to downregulate CD4 in the context of HIV‐1 infection in primary T cells . In addition to the well‐established role of AP‐2 in Nef‐mediated endocytosis of CD4, other host factors are likely involved in this process.…”
Section: Nef Hijacks Clathrin‐mediated Protein Transport Pathwaysmentioning
confidence: 99%
“…Recently, AP‐2 has been confirmed as the crucial AP complex hijacked by Nef to downregulate CD4 in the context of HIV‐1 infection in primary T cells . In addition to the well‐established role of AP‐2 in Nef‐mediated endocytosis of CD4, other host factors are likely involved in this process.…”
Section: Nef Hijacks Clathrin‐mediated Protein Transport Pathwaysmentioning
confidence: 99%
“…Evidence obtained by our group and others suggests the participation of ACOT8 in Nef‐mediated down‐regulation of CD4 and MHC‐I . Mutations located at the Nef core, L110A, PD122AA, and D123 are important for both ACOT8 binding and degradation of CD4 and MHC‐I receptors in SupT‐1 T cell line . However, the observation that Nef Δ17‐26 still binds to CD4 but loses its ability to associate with ACOT8 suggests that similar, albeit not identical, Nef domains are involved in the interaction with CD4 and ACOT8.…”
Section: Acot8‐nef Functionsmentioning
confidence: 77%
“…FACS‐FRET assays performed by our group confirmed the previous data, revealing significant FRET signals with Nef‐NA7, and Nef‐NL43 alleles, but not with HIV‐2 nor nonhuman primate Nef alleles. Subsequently, similar experiments with different Nef mutants showed that L110A and PD122AA mutations located in the hydrophobic core of the viral protein abolished the interaction with ACOT8 . Interestingly, the Nef region between residues 123‐152 is one of the immunogenic domains involved in proteasomal digestion, more specifically the region from 128 to 135, which is one of the major cleavage products.…”
Section: Acot8 and Nef Interactionmentioning
confidence: 90%
“…It took a long time to work out the functions of NEF in the HIV-1 life cycle, and I am not certain that even now we know the full story [11,12,13,14,15,16]. I had noted that the nef gene ends in a UGA termination codon, which allows readthrough of the terminator and insertion of a selenium-containing tRNA (SeCystRNA) into an extension protein.…”
Section: Commentary Articlementioning
confidence: 99%